193k views
5 votes
Subtract (5y3 + 6y + 3y4) from (4y4 - 8y3)

2 Answers

4 votes

Answer: = y^4-3y^3+6y

Explanation:

Subtract 3y^4 from 4y^4.

=y^4-8y^3+5y^3+6y

Add -8y^3 and 5y^3.

=y^4-3y^3+6y

*Remember you can only add or subtract like terms*

User Shubho Shaha
by
4.7k points
6 votes

Good evening ,

______

Answer:

= y⁴ - 13y³ -6y

___________________

Explanation:

Look at the photo below for the answer.

:)

Subtract (5y3 + 6y + 3y4) from (4y4 - 8y3)-example-1
User User Rebo
by
5.1k points